2018
DOI: 10.1177/1098612x18774709
|View full text |Cite
|
Sign up to set email alerts
|

Feline injection site sarcoma: immunohistochemical characteristics

Abstract: Objectives Feline injection site sarcoma (FISS) is a rapid growing locally aggressive tumor with a low metastatic rate. Its histologic features are clearly defined, but there are few studies regarding its immunohistochemical characteristics. The present study investigated the immunohistochemical characteristics of 21 cases of FISS. Methods FISSs from 12 male and nine female cats, 20 mixed-breed and one Siamese, were included in the study. After histopathological diagnosis, additional histologic sections were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 32 publications
3
30
0
1
Order By: Relevance
“…The authors conclude that these findings may be useful in predicting the sensitivity of FISS to treatment with COX-2 inhibitors, but their potential therapeutic use could be restricted to tumours with a lower degree of anaplasia. These results were in accordance with those of the investigations of Magi et al (35) and Carneiro et al (11), who found COX-2 expression in 97.0% (30/31) and 61.9% (13/21) of FISS cases, respectively, but in contrast to those of Beam et al (7), who did not find COX-2 expression in any FISS cases.…”
Section: Expression Of Cox-2 In Canine and Feline Tumourssupporting
confidence: 92%
See 1 more Smart Citation
“…The authors conclude that these findings may be useful in predicting the sensitivity of FISS to treatment with COX-2 inhibitors, but their potential therapeutic use could be restricted to tumours with a lower degree of anaplasia. These results were in accordance with those of the investigations of Magi et al (35) and Carneiro et al (11), who found COX-2 expression in 97.0% (30/31) and 61.9% (13/21) of FISS cases, respectively, but in contrast to those of Beam et al (7), who did not find COX-2 expression in any FISS cases.…”
Section: Expression Of Cox-2 In Canine and Feline Tumourssupporting
confidence: 92%
“…Queiroga et al (48) examined the prognostic value of COX-2 expression in malignant canine mammary tumours in 27 bitches also through evaluation of correlation with clinico-pathological parameters such as tumour size, histological type, presence of necrosis, metastases to lymph nodes, and PFS and OS. COX-2 expression was found in all cases over a broad range of IHS scores (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), but was predominantly noted at scores for stronger expression intensity (average IHS 8.8). Expression of COX-2 was significantly higher in tumours with metastases to lymph nodes, but a correlation between COX-2 expression and tumour size, histological type, or presence of necrosis was not noticed.…”
Section: Cox-2 As a Biomarker With Diagnostic Therapeutic Prognostic And Predictive Relevancementioning
confidence: 94%
“…There were no significant differences in sex between cats with FISS, which agrees with data reported for these tumours in studies with a higher number of cases 9,26 . However, the average age of cats at the time of sarcoma diagnosis was higher than that reported in other studies, which showed the involvement of younger cats, but similar to a Brazilian study with an average of 10 years 25‐28 .…”
Section: Discussionsupporting
confidence: 88%
“…Histologically, FISS are usually characterised by strand‐like proliferations of spindle‐shaped tumour cells with necrotic areas and infiltrations of multinucleated giant cells 6. In case of previous vaccinations, the giant cells can contain greyish material often interpreted as aluminium‐based adjuvant 7 21…”
Section: Discussionmentioning
confidence: 99%
“…Associated with injection fibrosarcomas are part of feline injection‐site sarcomas (FISS) and develop in 1–10 of 10,000 vaccinated cats 4 5. FISS are mesenchymal neoplasms that include malignant fibrous histiocytomas, osteosarcomas, chondrosarcomas, rhabdomyosarcomas, liposarcomas and undifferentiated sarcomas 6. For differentiation between the various neoplasms associated with FISS, different immunohistochemical markers are necessary.…”
Section: Introductionmentioning
confidence: 99%